MODELLING THE SIGNIFICANCE OF GLOBAL MIND-SET AND HALAL BRAND TRUST TO DETERMINE THE PERFORMANCE OF HALAL SMES - Marvello, Yang; Norizan, Jaafar; Sin, Kit Yeng (International Journal of Business and Society (IJBS), 2022)
This study investigated the impact of global mind-set (GM) and halal brand trust (HBT) on halal entrepreneurial performance (HEP). This study extends the entrepreneurship literature by adopting the dynamic capability theory (DCT) to assess HEP. Data were collected from 311 SMEs established in Indonesia using the simple random sampling method, whereas the variance-based partial least-square structural equation modelling (PLS-SEM) approach was used for test the proposed conceptual model. This study revealed the significant effect of GM and HBT upon HEP. Additionally, entrepreneurial competency (EC) and effectual logic (EL) displayed partially mediating effects. This study found that online food delivery (OFD) had strengthened the relationship between EC and HEP. Nevertheless, EC had no statistical impact on EL, while OFD negatively affected the GM-HEP link. Due to the limited scope of this study, the cross-sectional approach adopted in this study is viewed as a limitation. Besides, constriction in time had led this study to be conducted within a specified time-frame. As such, future studies may adopt the longitudinal approach over a period of three to five years in order to overcome the listed limitations. This study assessed the effect of GM and HBT on HEP as fresh insight to better comprehend the determinants of HEP in uncertain condition. This study has extended the theory of Teece et al. (1997) DCT within the context of HEP. Upon determining the effect of two new constructs (GM and HBT) through the lens of DCT and validating the proposed model, this study offers theoretical and contextual contributions to the overall body of knowledge with PLS-SEM.